2016
DOI: 10.1007/s00261-016-0930-5
|View full text |Cite
|
Sign up to set email alerts
|

Through thick and thin: a pictorial review of the endometrium

Abstract: The purpose of this pictorial review is to describe the normal appearance of the endometrium and to provide radiologists with an overview of endometrial pathology utilizing case examples. The normal appearance of the endometrium varies by age, menstrual phase, and hormonal status with differing degrees of acceptable endometrial thickness. Endometrial pathology most often manifests as either focal or diffuse endometrial thickening, and patients frequently present with abnormal vaginal bleeding. Endovaginal ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Ultrasound is widely used to assess endometrium and there are different features for different phases of endometrium. [24] However, different phases of endometrium are mainly differentiated by endometrial thickness while this study shows OCTIS could demonstrate endometrial glands which could add information on the assessment of different phases of endometrium. In addition, the OCTIS machine used in our study can obtain real-time images without delay as it took 10 to 30 seconds for the endometrium evaluation in the above study [17] that render clinical use of OCTIS.…”
Section: Discussionmentioning
confidence: 73%
“…Ultrasound is widely used to assess endometrium and there are different features for different phases of endometrium. [24] However, different phases of endometrium are mainly differentiated by endometrial thickness while this study shows OCTIS could demonstrate endometrial glands which could add information on the assessment of different phases of endometrium. In addition, the OCTIS machine used in our study can obtain real-time images without delay as it took 10 to 30 seconds for the endometrium evaluation in the above study [17] that render clinical use of OCTIS.…”
Section: Discussionmentioning
confidence: 73%
“…The assessment of the endometrial condition is a critical component of routine gynecological examinations 1 . This includes evaluating its thickness, 2 texture, 3 and the presence of any intrauterine space-occupying lesions 4 . Consequently, the precise delineation of the endometrial area provides essential information for medical diagnosis, influencing the choice of treatment and its outcomes 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Normal embryos and healthy uteri are two necessary factors for a successful pregnancy 1 . The recent, continuous increase in induced abortions, uterine cavity operations, and the functional defects in endometrial stem/progenitor cells are believed to be responsible for thinning endometrium (< 7 mm) 2 . It has been reported that the thin endometrium is a defect of endometrial development and is associated with low embryo implantation rates 3 6 .…”
Section: Introductionmentioning
confidence: 99%